Zn situation of vegetable garden soils and its relation to soil organic carbon - NI Wu-zhong; LONG Xin-xian; SUN Qin; HE Ji-xiu; YABG Xiao-e (浙江大学学报. 农业与生命科学版, 2000)
With a field survey, Zn situation of vegetable garden soils and its relation to soil organic carbon were investigated. The results presented that the total Zn contents of vegetable garden soils in the survey area range 75.5-302.0 mg/kg with an average as (168.1±58.0) mg/kg, and the available Zn contents range 0.78-9.15 mg/kg with an average as (3.90±2.01) mg/kg. And it was found that there was significant correlativity between the available Zn content and the total Zn content, implying that the supply of available Zn in vegetable garden soils is based on the total Zn. It can also be obtained that the total Zn content of the vegetable garden soil was significantly correlative to the contents of TOC (Total organic carbon) and EOOC (Easily - oxidized organic carbon), and so was the available Zn content. These results mean that organic manure may be one of the main sources of Zn nutrient of vegetable garden soils.